Human Values In Maqamat Badiuzzaman Al-Hamdani - Laily Fitriani (Journal of Arabic Literature (JaLi), 2019)
Abbasiyah time was a golden period in the era of glory in all fields of science. This time was marked by the development of religious and non-religious sciences, as well as literature. Maqamat art was one type of Abbasiyah prose that experienced rapid development, with Badiuzzaman al-Hamdani as a figure whose maqamat work consist of human values. Maqamat is a short story that contains the events of the main characters narrated by certain narrators. The language style is mostly in the form of 'and badi' and ends with advice.This study purposes to describe the characteristics in Badiuzzaman al-Hamdani’s Maqamat and explain human values in Badiuzzaman al-Hamdani’s Maqamat. Data collection is conducted with documentations and heuristic techniques and analyzed qualitatively. The results of the study explain: 1) Five characteristics in Badiuzzaman al-Hamdani’s Maqamat consist of themes, characterizations, plot, background and point of view, and 2) Moral values portrayed in Badiuzzaman al-Hamdani’s Maqamat are human values and justice values. Keywords: Badiuzzaman al-Hamdani’s Maqamat, characteristics, content analysis, moral values